Pengaruh Manajemen Laba, Kinerja Perusahaan dan Ukuran Perusahan terhadap Keputusan Reklasifikasi Aset Keuangan pada Perusahaan Perbankan di Indonesia - Sparta Sparta; Suci Handini (STIE Indonesia Banking School, 2015)
This study aims to determine wheter the company’s decision to reclassify their financial assets is affected by earnings management, company’s performance, and company’s size. This research also aims to determine wheter the earnings management practices are differences before and after the implementation of (2006) amendment of PSAK No.55.The results shows that: (1) There’s a simultaneously effect of income smoothing, accrual earnings management, company’s performance, and company’s size to reclassification probabilities; (2) Accrual earnings management and company’s size have partial significant effect to reclassification probabilities; (3) Income smoothing and company’s performance don’t have partial significant effect to reclassification probabilities; (4) There’s no differences in income smoothing before and after the implementation of (2006) amendment of PSAK No.55.